GERAKAN VER-HANG (VERTIGO HANGINGPLANT) UNTUK PEMANFAATAN SAMPAH BOTOL PLASTIK DI DUKUH SELO TAWANGSARI SUKOHARJO - Sani Kamil Baldan; Aditiya Aditiya; Vera Febriana Umiati; Tinon Yudhiana; Diana Nur Hafifah; Rysca Indreswari (Universitas Muhammadiyah Semarang, 2018)
Waste plastic bottles often become a prolonged problem in every area. Process recycling to reduce population can be done by making use of disused plastic bottles as planting media vertikultur. The background of the abundance of junk of disused plastic bottles that are buried in the bank trash dukuh Selo and a nursery of plants that are less walking and antusiame communities in building the village. Movement of Ver-Hang has a purpose in order to improve awareness of recycling of disused plastic bottles that were previously only sold just become a more profitable business venture. The method used is a Participatory Rural Appraisal (PRA). Participatory Rural Appraisal is a method of approach in the process of empowerment and increased participation of the community. Stages in the form of socialisation making vertikultur making, socialization, as well as business training makrame and effort. Commercial analysis of a product is done to find out the feasibility of product sales hangingplant. Through the analysis of R/C proved that the products worth hangingplant to commercialized. The result of the movement of the Ver-Hang change mindsets of society and increasing the motivation of community after the existence of the program to be more creative in utilizing the bottles. The success of this movement is shown by the growing motivation of the community, demonstrated through the analysis of wilcoxon test. In the end it can be concluded that this movement can be the best solution in utilising disused plastic bottles into a vertical garden that has aesthetic and commercial side of the highly profitable. Keywords: plastic bottles, Hangingplant, Commercialization